HMI/ SCADA standards in the design of data center interfaces: A network operations center case study (2015)
This paper presents an evaluation of interfaces at the Network Operations Center NOC (Network Operations Center) in terms of HMI standards and related regulations, as well as the ergonomic monitoring GEDIS guide. The Centre of Operations NOC at the Institute of technology and renewable energy (ITER) is responsible for monitoring the various infrastructures of the Data Centre such as the air conditioning, power supply, fire protection, security, technical centers, wind farms, photovoltaic plants, and different infrastructures deployed around the submarine cable belonging to the Consortium Cana-Link (the cable that connects the mainland and Canary Islands, the earth ring and the Network IRIS). To unify systems and facilitate the NOC personal’s daily tasks, the ITER has been using the BMS system for SCADA software. However, BMS is a software specialist in the management of buildings, and as such BMS software was substituted by the new specialized system designed after this evaluation.